Association of C-Reactive Protein with Short-Term Outcomes in Spontaneous Intracerebral Hemorrhage Patients with or without Infection: From a Large-Scale Nationwide Longitudinal Registry - Du Y; Liu L; Kang K; Lin Y; Gu H; Bian L; Li Z; Zhao X (Clinical Interventions in Aging)
Yang Du,1,2 Lijun Liu,1,2 Kaijiang Kang,1,2 Yijun Lin,1,2 Hongqiu Gu,1,2 Liheng Bian,1,2 Zixiao Li,1,2 Xingquan Zhao1– 4 1Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2China National Clinical Research Center for Neurological Diseases, Capital Medical University, Beijing, People’s Republic of China; 3Research Unit of Artificial Intelligence in Cerebrovascular Disease, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 4Center of Stroke, Beijing Institute for Brain Disorders, Beijing, People’s Republic of ChinaCorrespondence: Xingquan Zhao; Zixiao Li, Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, 119 West Road, South 4th Ring, Fengtai District, Beijing, People’s Republic of China, 100070, Tel +86-10-59975835, Email lizixiao2008@hotmail.com; zxq@vip.163.comAim: To study the relationship between elevated C-reactive protein (CRP) levels, infection, and spontaneous intracerebral hemorrhage (ICH) outcomes.Methods: Patients were classified into four groups (Q1–Q4). Logistic regression was used to analyze the relationship between different CRP levels and functional disability (mRS score of 3– 5) at discharge, intracerebral hematoma evacuation, and in-hospital mortality. Subgroup analysis was conducted on patients with or without infection during hospitalization.Results: A total of 14,529 patients with ICH were enrolled in this study. In the multivariate logistic regression model, compared with the reference CRP quartile group (Q1), the Q4 group had a higher proportion of functional disability (adjusted OR, 1.30, 95% CI 1.16– 1.45) and hematoma evacuation (adjusted OR, 1.88, 95% CI 1.58– 2.23). In patients without infection, compared with the Q1 group, the Q4 group had a higher risk of functional disability (adjusted OR, 2.16, 95% CI 1.71– 2.73) and hematoma evacuation (adjusted OR, 1.15, 95% CI 1.00– 1.31).Conclusion: A significantly increased CRP level was associated with a higher risk of early functional disability and hematoma evacuation in patients with ICH, regardless of the presence or absence of infectious complications. Infection may increase the risk of poor outcomes in patients with ICH, but caution is needed when facing abnormally high CRP levels in patients with ICH without infection. Keywords: C-reactive protein (CRP), infection, inflammation, spontaneous intracerebral hemorrhage, poor outcome